Dicer-Like Genes Are Required for H2O2 and KCl Stress Responses, Pathogenicity and Small RNA Generation in Valsa mali - Feng, Hao; Xu, Ming; Liu, Yangyang; Dong, Ruqing; Gao, Xiaoning; Huang, Lili (Frontiers in Microbiology, 2017)
Valsa mali (V. mali) is the causative agent of apple tree Valsa canker, which heavily damages the production of apples in China. However, the biological roles of the RNA interfering (RNAi) pathway in the pathogenicity of V. mali remain unknown. Dicer-like proteins (DCLs) are important components that control the initiation of the RNAi pathway. In this study, VmDCL1 and VmDCL2 were isolated and functionally characterized in V. mali. VmDCL1 and VmDCL2 are orthologous in evolution to the DCLs in Cryphonectria parasitica. The deletion of VmDCL1 and VmDCL2 did not affect vegetative growth when the mutants (△VmDCL1, △VmDCL2 and △VmDCL1DCL2) and wild type strain 03-8 were grown on a PDA medium at 25°C in the dark. However, the colony of △VmDCL1 increased by 37.1% compared to the 03-8 colony in a medium containing 0.05% H2O2 3 days after inoculation, and the growth of △VmDCL1 was significantly inhibited in a medium containing 0.5 M KCl at a ratio of 25.7%. Meanwhile, in the presence of 0.05% H2O2, the growth of △VmDCL2 decreased by 34.5% compared with the growth of 03-8, but △VmDCL2 grew normally in the presence of 0.5 M KCl. More importantly, the expression of VmDCL2 was up-regulated 125-fold during the pathogen infection. In the infection assays using apple twigs, the pathogenicity of △VmDCL2 and △VmDCL1DCL2 was significantly reduced compared with that of 03-8 at a ratio of 24.7% and 41.3%, respectively. All defective phenotypes could be nearly rescued by re-introducing the wild type VmDCL1 and VmDCL2 alleles. Furthermore, the number and length distribution of unique small RNAs (unisRNAs) in the mutants and 03-8 were analyzed using deep sequencing. The number of unisRNAs was obviously lower in △VmDCL1, △VmDCL2 and △VmDCL1DCL2 than that in 03-8, and the length distribution of the sRNAs also markedly changed after the VmDCLs were deleted. These results indicated that VmDCLs function in the H2O2 and KCl stress response, pathogenicity and generation of sRNAs.